A group of SUVH methyl‐DNA binding proteins regulate expression of the DNA demethylase ROS1 in Arabidopsis. Issue 2 (1st February 2019) - Xiao, Xinlong; Zhang, Jieqiong; Li, Tao; Fu, Xing; Satheesh, Viswanathan; Niu, Qingfeng; Lang, Zhaobo; Zhu, Jian‐Kang; Lei, Mingguang
Abstract: DNA methylation is typically regarded as a repressive epigenetic marker for gene expression. Genome‐wide DNA methylation patterns in plants are dynamically regulated by the opposing activities of DNA methylation and demethylation reactions. In Arabidopsis, a DNA methylation monitoring sequence (MEMS) in the promoter of the DNA demethylase gene ROS1 functions as a methylstat that senses these opposing activities and regulates genome DNA methylation levels by adjusting ROS1 expression. How DNA methylation in the MEMS region promotes ROS1 expression is not known. Here, we show that several Su(var)3‐9 homologs (SUVHs) can sense DNA methylation levels at the MEMS region and function redundantly to promote ROS1 expression. The SUVHs bind to the MEMS region, and the extent of binding is correlated with the methylation level of the MEMS. Mutations in the SUVHs lead to decreased ROS1 expression, causing DNA hypermethylation at more than 1, 000 genomic regions. Thus, the SUVHs function to mediate the activation of gene transcription by DNA methylation. Abstract : A DNA methylation monitoring sequence (MEMS) in the promoter of ROS1 functions as a methylstat that senses DNA methylation level and regulates active demethylation activity. However, the mechanism is unknown. Here, we unequivocally prove that several Su(var)3‐9 homologs recognize DNA methylation at the MEMS region and function redundantly to promote demethylase ROS1 gene expression.